TRAINING EFFCT DURING THE MIDNIGHTSUN PERIOD IN DIFFERENT CHRONOTYPES - Weydahl, Andi (UiT The Arctic University of Norway, 2017)
Poster presentation Our research takes place at 70oN. Where the sun is above the horizon for 8 weeks during summer, midnight sun and below the horizon for 8 weeks during winter, polar night. Earlier we found that adults with different chronotypes responded differently to exercise performed in day-light or darkness1. During the polar night evening (E) and neither (N) -types respond to training better than morning (M) –types2. This study reports the effect of training during the midnight sun period in individuals with different chronotypes.